Parallel impurity dynamics in the TJ-II stellarator. (10th June 2016) - Alonso, J A; Velasco, J L; Calvo, I; Estrada, T; Fontdecaba, J M; García-Regaña, J M; Geiger, J; Landreman, M; McCarthy, K J; Medina, F; Van Milligen, B Ph; Ochando, M A; et al.
Abstract: We review in a tutorial fashion some of the causes of impurity density variations along field lines and radial impurity transport in the moment approach framework. An explicit and compact form of the parallel inertia force valid for arbitrary toroidal geometry and magnetic coordinates is derived and shown to be non-negligible for typical TJ-II plasma conditions. In the second part of the article, we apply the fluid model including main ion-impurity friction and inertia to observations of asymmetric emissivity patterns in neutral beam heated plasmas of the TJ-II stellarator. The model is able to explain qualitatively several features of the radiation asymmetry, both in stationary and transient conditions, based on the calculated in-surface variations of the impurity density.